Coxa magna and severe osteoarthrosis in an adult male from the Bronze Age necropolis Torre Velha 3 (Serpa, Portugal). (August 2020) - Fidalgo, Daniel; Silva, Ana Maria
Highlights: Bronze Age male adult affected by unilateral severe osteoarthrosis and coxa magna. Differential diagnosis inconclusive, given the condition development since childhood. Skeletal analysis suggests long-term movement impairment. We infer social care implications during the Southwestern Iberian Bronze Age. Abstract: A middle-age adult male from the Bronze Age necropolis Torre Velha 3 (Serpa, Portugal) shows an enlarged right femoral head ( coxa magna ) with severe osteoarthrosis, and compatible changes on the right acetabulum. Using macroscopic and X-ray analysis, we discuss its possible aetiology as Legg-Calvé-Perthes, slipped femoral capital epiphysis, congenital hip dislocation, osteomyelitis or trauma. The results were inconclusive, given the lack of clinical data, and the challenge of analysing pathological conditions that developed during childhood in mature skeletal remains. Nonetheless, it is possible that this individual had an abnormal gait, which impacted his daily activities, besides having benefited from help from members of his community.